Current situation and considerations on Traditional Chinese Medicine nursing in nutritional management for diabetes mellitus (中医护理在糖尿病营养管理中的应用现状及思考) - HAO Yangyang (郝杨杨) (中西医结合护理)
Diabetes mellitus is a common clinical condition, and nutritional management is one of the indispensable aspects in the treatment of diabetic patients. Traditional Chinese Medicine nursing provides personalized nutrition management plan for diabetic patients through various measures such as dietary conditioning, Traditional Chinese Medicine application, acupuncture therapy and emotional regulation. This paper studies the application of Traditional Chinese Medicine in the nutritional management of diabetes mellitus and develops promotion strategies to improve the acceptance and compliance of Traditional Chinese Medicine care among diabetic patients. (糖尿病是临床常见病, 营养管理是糖尿病患者治疗过程中不可或缺的环节之一。中医护理通过饮食调理、中药应用、针灸疗法和情志调节等多种措施, 为糖尿病患者提供了个性化的营养管理方案。本研究就糖尿病营养管理背景、中医护理在糖尿病营养管理中的应用现状以及作用机制进行综述, 旨在为糖尿病患者的营养管理提供更多可靠参考。)